PERANCANGAN FILM CERITA PENDEK PENTINGNYA PERTIMBANGAN KETIKA PEMUDA MINANG MERANTAU - RIDHO PRATAMA PUTRA, Dini Faisal, S.Ds., M.Ds., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Generally, when a young man goes out of his hometown to other city, it is called as Merantau. On the other hand, in Minangkabau tradition, Merantau is when a young man goes out from Luhak Nan Tigo to Rantau city. Nevertheless, it is not as easy as people think to Merantau, because it should have a consideration for someone, especially young man, to go to Merantau. In some case, a family which is only lived a mother and the only one son, does the son go to Merantau or stay to take care his mother.The objective of this film planning was not only delivering the information about Merantau in Minangkabau tradition, but also showing mother’s feeling who was left by her son to Merantau. Thus, the Minang young man can be more considered before going to Merantau to leave his mother.This planning will be informed by film as a media. Film is chosen as media because it can be expected as one of strong media for delivering information; it has two factors, audio and visual. Story in a film usually is inspired from slice of life story. The method for this film planning was a research method with theory R&D step (4-D), and the data was found by interview and observation. For data analysis, it was used 5W + 1H (what, where, why, who, when, + How).Key Words: Merantau, Film, Production